Desempenho e segurança da anfotericina b lipossomal (AmBisome®) no tratamento de indivíduos com leishmaniose tegumentar americana : uma série de casos - Alves, Sabrina Mendonça Marçal (2018)
American Cutaneous Leishmaniasis (ACT) is a zoonotic, rural and peri-urban disease caused by obligate intracellular protozoa of the genus Leishmania, transmitted by insects of the genus Lutzomyia. Pentavalent antimonials are the first line therapy, but they cause serious side effects, mainly on the electrical function of the heart, being contraindicated in heart patients, nephropathies, liver disease patients, pregnant women and people over 50 years of age. In this scenario, the use of liposomal amphotericin b (AmBisome® ) has been proposed, safer and more effective. However, there are few reports on its safety and performance in the literature, with few short series of cases, and an ideal therapeutic regimen that is still undefined. This study had as goal to analyze the safety and performance of amphotericin b liposomal (AmBisome® ) in the treatment of ACT, contributing to the debate among the scientific community and stimulating the publication of similar experiences. Of the total sample of 34 patients, 19 (64,7%) presented side effects to the use of Ambisome® , with low clinical repercussion, being well tolerated in most patients. The main side effect was increased urea, creatinine and ions, manageable during treatment. There was clinical cure in 31 patients (91,1%), treatment failure in two patients (5,9%), and death due to other causes in one patient (3%). It is wellknown that the performance of the drug may be related to longer treatment regimens, allowing for adjustable doses in each clinical situation. Daily and total doses appeared to have no effect on treatment performance. It is concluded that liposomal amphotericin B is the safest and most effective drug among leishmanicides and the best therapeutic option for clinical contraindications to pentavalent antimonial.